Nighttime Ionospheric TEC Study Over Latin America During Moderate and High Solar Activity. Issue 10 (25th September 2020) - Romero‐Hernandez, E.; Denardini, C. M.; Jonah, O. F.; Essien, P.; Picanço, G. A. S.; Nogueira, P. A. B.; Rodriguez‐Martinez, M.; Resende, L. C. A.; de la Luz, V.; Aguilar‐Rodriguez, E.; Sergeeva, M.; Gonzalez‐Esparza, J. A.; et al.
Abstract: The present work is a comprehensive study of the ionospheric vertical total electron content (vTEC) variations during the nighttime, based on data collected by ground‐based Global Navigation Satellite System (GNSS) receivers over the Latin American region. We provide a qualitative and quantitative analysis of the ionospheric vTEC trend at 21:00, 00:00, and 03:00 local time (LT), during geomagnetically undisturbed days of 2011 (ascending phase) and 2014 (maximum phase), which encompassed (a) the response to the solar flux variation, (b) the seasonal trend in different latitudes and longitudes, and (c) the interhemispheric asymmetry. One significant result of this study is the development of TEC maps for the Latin American region, which are used for the monitoring and forecasting of the ionosphere for space weather purposes. The nighttime vTEC variations showed a strong latitudinal dependence, especially in the Northern Hemisphere. For 2011, the semiannual anomaly was similar to that observed in daytime; however, in 2014, the receivers at midlatitude presented asymmetric behavior. Similarly, the nighttime winter anomaly (NWA) was very weak in both years. The Equatorial Ionospheric Anomaly (EIA) signature was absent from June to August, a period in which the hemispheric disparity in the vTEC values became more evident, suggesting a feeble interhemispheric circulation. The Midlatitude Summer Nighttime Anomaly (MSNA) was also identified in the Southern Hemisphere, during January and February of 2011 (moderate solar activity). Model approximations suggest that the equatorward winds and the EIA were involved in the formation of the MSNA. Key Points: TEC maps for the Latin American region have been developed as a tool for analyzing the spatial and temporal nighttime ionosphere variations The MSNA was analyzed in terms of downward plasma fluxes and equatorward winds registered during January and December The seasonal variability of the ionosphere over this region, including the EIA and the MSNA, became no longer significant after midnight